The Alphonso Lingis reader - Lingis, Alphonso, 1933- (University of Minnesota Press, 2018)
"The Alphonso Lingis Reader showcases the philosophical thought and beautiful writing of Alphonso Lingis across his career. Much of his writing is a unique blend of travelogue, cultural anthropology, and philosophy"--